2021
DOI: 10.1073/pnas.2109481118
|View full text |Cite
|
Sign up to set email alerts
|

Societal shifts due to COVID-19 reveal large-scale complexities and feedbacks between atmospheric chemistry and climate change

Abstract: The COVID-19 global pandemic and associated government lockdowns dramatically altered human activity, providing a window into how changes in individual behavior, enacted en masse, impact atmospheric composition. The resulting reductions in anthropogenic activity represent an unprecedented event that yields a glimpse into a future where emissions to the atmosphere are reduced. Furthermore, the abrupt reduction in emissions during the lockdown periods led to clearly observable changes in atmospheric composition,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 75 publications
(81 reference statements)
5
37
1
Order By: Relevance
“…These lockdowns relaxed in the second half of 2020 and OH could have recovered. Laughner et al (2021) found in a box model analysis that a 3% reduction in global mean OH concentration in 2020 could account for only half of the observed methane increase, which is consistent with our results that OH changes cannot explain most of the 2020 methane surge. Stevenson et al (2021) argue that most of the methane increase from 2019 to 2020 is due to a 15% reduction in global NO x emissions, based on model sensitivities of methane to NO x , but they did not consider the offsetting impact of reductions in CO emissions (Fry et al 2012).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These lockdowns relaxed in the second half of 2020 and OH could have recovered. Laughner et al (2021) found in a box model analysis that a 3% reduction in global mean OH concentration in 2020 could account for only half of the observed methane increase, which is consistent with our results that OH changes cannot explain most of the 2020 methane surge. Stevenson et al (2021) argue that most of the methane increase from 2019 to 2020 is due to a 15% reduction in global NO x emissions, based on model sensitivities of methane to NO x , but they did not consider the offsetting impact of reductions in CO emissions (Fry et al 2012).…”
Section: Resultssupporting
confidence: 92%
“…COVID-19 shutdowns in 2020 were a major perturbation to economic activity but the effect on methane is unclear. Oil/gas production declined which would be expected to decrease methane emission in some regions (Lyon et al 2021), but reduced maintenance of infrastructure could have caused increases (Laughner et al 2021).Decreases in emissions of nitrogen oxides (NO x ≡ NO + NO 2 ) from fuel combustion led to decreases in free tropospheric ozone (Bouarar et al 2021, Steinbrecht et al 2021, which would decrease OH concentrations (Miyazaki et al 2021) and hence the methane sink (Laughner et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to surveys conducted by the World Meteorological Organization, a U.N. agency, the economic slowdown caused by COVID-19 and the resulting lockdowns has had no visible impact on the atmospheric levels of greenhouse gases and their growth rates [107,108]. It is likely that the slowdown in emissions has begun to be counterbalanced by the effects of the four phenomena outlined above, which indicates that the prospects for humanity are not encouraging.…”
Section: Thawing Of the Tundramentioning
confidence: 99%
“…In addition, major new mobility trends in urban transport are unfolding globally causing potential health effects due to traffic-related air pollution. The unprecedented economic shutdowns due to the global COVID-19 pandemic over the past two years have made more visible the impacts of anthropogenic activities on air pollution and provided an unexpected opportunity to understand what the world can do better with regards to improved air quality. With this background, this Special Issue aimed to synthesize the latest multidisciplinary advances on urban air quality, its sources, its chemistry and microbiology, health impacts and disease implications, solutions for mitigation and control, and research outcomes influencing policy change. New developments were occurring during the call for submissions for the Special Issue, brought into action by the World Health Organization’s recommendation of more stringent guideline values on key air pollutants in September 2021 .…”
Section: Historical Contextmentioning
confidence: 99%